Duodenal diverticulitis masquerading as acute cholecystitis: A lesson learnt. Issue 4 (15th November 2019) - Khan, Amena; Karanth, Veena; Khan, Afroz; Rodrigues, Gabriel
Abstract : Acute cholecystitis is one of the common surgical emergencies encountered in daily practice. Clinical examination coupled with an ultrasound scan of the abdomen will usually confirm the diagnosis. The rare presence and inflammation of a duodenal diverticula can mimic acute cholecystitis and lead to a diagnostic dilemma that can result in a surgical catastrophe. We present a case of a 62‐year‐old lady with a provisional diagnosis of acute cholecystitis, which turned out to be duodenal diverticulitis, who did not respond to conservative management and was successfully managed surgically.